If it's not what You are looking for type in the equation solver your own equation and let us solve it.
54=(4x+6)(2x)
We move all terms to the left:
54-((4x+6)(2x))=0
We calculate terms in parentheses: -((4x+6)2x), so:We get rid of parentheses
(4x+6)2x
We multiply parentheses
8x^2+12x
Back to the equation:
-(8x^2+12x)
-8x^2-12x+54=0
a = -8; b = -12; c = +54;
Δ = b2-4ac
Δ = -122-4·(-8)·54
Δ = 1872
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{1872}=\sqrt{144*13}=\sqrt{144}*\sqrt{13}=12\sqrt{13}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-12)-12\sqrt{13}}{2*-8}=\frac{12-12\sqrt{13}}{-16} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-12)+12\sqrt{13}}{2*-8}=\frac{12+12\sqrt{13}}{-16} $
| t+11/2=-4 | | 6x^2-18x-98=0 | | 18n+-11n-18=-3 | | 20+7h=6h | | 3b+5=6b-3b+8-9 | | 5k-10=7k+8 | | -18=-3(h-9) | | (X+4)+3(5-2x)=11 | | 20-9k=-20+11k | | 15n-6n=9 | | 9w+10=w-10+10w | | 10r=-7+11r | | 4x/3x-12=1/x-4 | | b/3+-15=-13 | | 3x+7=14+2.5x | | x-31/8=98/9 | | 3/5x+1=-20 | | -45=3(2x+3) | | -8t=-38 | | 12x+17x=7 | | 18x2+12=6x2+4 | | 5w-4w=-8 | | -2x+33=4(5x-4)+5 | | 2a+9=7-a+5 | | 4x-6x-12=0 | | -2-8q=-6q-10 | | 4(2x+1)-2=-2x-38 | | r-3r=-14-4r | | 3/4x-8=22 | | -19=15-3a-11 | | v+6/4=3 | | 4v–v=12 |